Facilitatory and inhibitory role of central amylin administration in the regulation of the gonadotropin-releasing hormone pulse generator activity in goats. (25th September 2020) - Kitagawa, Yuri; Sasaki, Takuya; Suzumura, Reika; Morishima, Ai; Tatebayashi, Ryoki; Assadullah,; Ieda, Nahoko; Morita, Yasuhiro; Matsuyama, Shuichi; Inoue, Naoko; Uenoyama, Yoshihisa; Tsukamura, Hiroko; et al.
Highlights: Pulsatile GnRH secretion is necessary to maintain reproductive functions. CTR signaling is associated with the regulation of GnRH pulses. Activation of CTR had both stimulatory and inhibitory effects on GnRH pulsatility. Central amylin-CTR signaling modulates the GnRH pulse generator activity. Abstract: Pulsatile gonadotropin-releasing hormone (GnRH) secretion is essential for regulating reproductive functions in mammals. GnRH pulses are governed by a neural mechanism that is termed the GnRH pulse generator. In the present study, we investigated the role of central calcitonin receptor (CTR) signaling in the regulation of the GnRH pulse generator activity in ovariectomized goats by administering amylin, an endogenous ligand for CTR, into the lateral ventricle. GnRH pulse generator activity was measured using multiple unit activity (MUA) recordings in the mediobasal hypothalamus. We analyzed changes in the interval of characteristic increases in MUA (MUA volleys). The MUA volley interval shortened immediately after amylin administration, followed by prolonged intervals. Double in situ hybridization for KISS1 (kisspeptin gene) and CALCR (CTR gene) revealed that low expression levels of CALCR were found in the arcuate kisspeptin neurons, which is suggested as the main population of neurons, involved in GnRH pulse generator activity. These results suggest that central amylin-CTR signaling has a biphasic role in the regulation of GnRH pulse generator activity by acting on cells other than the arcuate kisspeptin neurons in goats.